PELATIHAN PEMBUATAN SEDIAAN INSTAN BAWANG DAYAK PADA IBU PKK KELURAHAN AIR PUTIH SAMARINDA - Dwi Lestari; Wirnawati Wirnawati; Fitriyanti Fitriyanti; Maulina Rahmawati Putri (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Dayak Onion has been used for generations by the Dayak community as a medicinal plant which is a medicine for various types of diseases such as breast cancer, high blood-lowering drugs (hypertension), diabetes (diabetes mellitus), cholesterol-lowering, boils, bowel cancer, preventing stroke. The aim of community service is to provide continuous training in making instant powder of Dayak onions with the specified standards so as to produce quality and worthy instant powder. The method of implementation includes licensing and introductions with the PKK of Air Putih village, the provisioning of Dayak onion planting and post-harvest technology, material on the technique of sorting the instant formula of dayak onions, making instant onions, the material and practice of packaging instant preparations. licensing and sales of Dayak onions, which are packed with counseling materials and brochures. For the manufacture of Onion Dayak Instant preparations in the UMKT Natural Materials Chemistry laboratory. Instant Onion Dayak preparations have the right formula so that it is suitable for use in household scale production processes. The ingredients are Dayak onions, granulated sugar, palm sugar, cinnamon and orange leaves. Cinnamon and orange leaves are used as a scent on preparations. Evaluation and monitoring also need to be done from the Kelurahan and facilitators from Muhammadiyah University of East Kalimantan to see the empowerment of PKK Air Putih Village mothers in economic independence related to the production of instant dayak onions. The next plan is to collaborate with the Samarinda City Industrial Office related to production and packaging guidance and licensing